2022
DOI: 10.3390/ijms23042338
|View full text |Cite
|
Sign up to set email alerts
|

Natural NADH and FAD Autofluorescence as Label-Free Biomarkers for Discriminating Subtypes and Functional States of Immune Cells

Abstract: Immune cell activity is a major factor for disease progression in inflammatory bowel diseases (IBD). Classifying the type and functional state of immune cells is therefore crucial in clinical diagnostics of IBD. Label-free optical technologies exploiting NADH and FAD autofluorescence, such as multiphoton microscopy, have been used to describe tissue morphology in healthy and inflamed colon samples. Nevertheless, a strategy for the identification of single immune cell subtypes within the tissue is yet to be dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The use of two different AF channels, enabled localization of distinct cells, that are linked to the immune response, as validated by MPO images. It was already shown that this approach can identify certain immune cell subtypes [6]. Although, these cells cannot specifically be identified in this study, the quantifiable observation of “MPM cell count” was highly correlated with the fibrotic score as discussed below.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The use of two different AF channels, enabled localization of distinct cells, that are linked to the immune response, as validated by MPO images. It was already shown that this approach can identify certain immune cell subtypes [6]. Although, these cells cannot specifically be identified in this study, the quantifiable observation of “MPM cell count” was highly correlated with the fibrotic score as discussed below.…”
Section: Resultsmentioning
confidence: 58%
“…When it is used in a label-free configuration, the signal is based on natural autofluorescence (AF) from cellular proteins, as well as on second harmonic generation (SHG) from molecules that lack inversion symmetry, such as collagen [5], a main constituent of fibrotic tissue. To some extent AF can be used to distinguish different cell types, based on their AF signatures [6,7], although it is not as specific as antibody staining. SHG imaging can be used for the noninvasive differentiation between active states in muscular motor-proteins [8] or the determination of the orientation angles of organic fiber structures [9], where the signal intensity is defined by the angle between laser polarization and structural orientation of SHG-active molecules [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in 2021, they demonstrated the ability of autofluorescence imaging to distinguish between quiescent and activated T-cells, as well as between the subsets of CD4+ and CD8+ cells [ 19 ]. Besides, the study by Lemire et al showed the increased NAD(P)H and FAD fluorescence intensity in stimulated CD4+, CD8+ and B-cells and the possibility to discriminate between the various types of innate and adaptive immune cells using autofluorescence intensity of the coenzymes [ 20 ]. However, in both studies the T-cell subsets were extracted from healthy donors and cultured in vitro, and the different activation states were modeled by adding non-antigenic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence lifetime imaging has been extensively used for metabolic investigations of cancer and other diseases [ 12 , 13 , 14 , 15 , 16 , 17 ]; however, the studies of immune cells using metabolic autofluorescence imaging is a very recent trend, and there are only a few studies so far [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in one study common intestinal epithelial cell types could be distinguished based on their overall morphology (Kreiß et al, 2020). Most recently these measures of metabolic activity have been used to identify immune cells in differing functional states during FACS ex vivo (Lemire et al, 2022). In this manuscript, we describe a live tissue explant system that permits label free cell type identification of both common and very rare epithelial cell types.…”
Section: Introductionmentioning
confidence: 99%